THE Efek Dari Strategi Mengajar Dosen Dan Gaya Belajar Siswa Terhadap Kemampuan Membacanya - Irawan; Dunifa, La; Una, Syamsul (English Education Journal, 2025)
Problem in this research was whether there is a positive and significant effects of teaching reading strategy and students’ learning style on reading performance. The objective of the research was to measure is there any positive significance the effect of teaching reading strategy and students’ learning style on reading performance at English education study program, Dayanu Ikhsanuddin University. This research method was survey design using path analysis approach. Population in this research was all of third semester students at English Education Study Program, Dayanu Ikhsanuddin University with total 40 students which was taken using total sampling technique. The instrument used was a questionnaire (Teaching Reading Strategy & Perceptual Learning Style) and test (TOEFL). This research found that there were: 1) the score of each lecturers’ teaching strategy questionnaire were 80.1% Reciprocal Teaching Strategy, 79% for SQ3R Strategy, 78.5% for Scaffolding Strategy, 77.3% for Think-Aloud Strategy and 75.9% for QARs Strategy. It indicated that one strategy (Reciprocal Teaching Strategy) is always category and four strategies (SQ3R Strategy, Scaffolding Strategy, Think-Aloud Strategy and QARs Strategy) are often category applied by EFL lecturers in teaching reading, 2) the average of each learning style questionnaire were 4.2 for Auditory, 4.2 for Kinesthetic and 4.0 for Visual Learning Style used by students, based on the high percentage of questionnaire, there was 85% or 34 students in major learning style category, it meant the students’ learning style was major learning style, 3) based on the high percentage of reading performance test, there was 65% or 26 students in fair category, it suggests the students’ reading performance was fair, 4) based on the result of hypothesis testing using independent sample T-test obtained fcount 7.951 and obtained significant value 0.001 < 0.005, with a positive effect 0.301 or 30.1% therefore Ha was accepted and H0 was rejected. Thus, it can be concluded that reading performance can be affected by teaching reading strategy and students’ learning style on third semester students at English Education Study Program, Dayanu Ikhsanuddin University.